Current trends in scientific research of sports training in freestyle - Ilyukhin I.A. ,; Zebzeev V.V. ,; Mironov A.Y. , (Theory and Practice of Physical Culture, 2025)
Objective of the study was to analysis of current trends in the field of scientific research on freestyle training. Methods and structure of the study. The research employed a combination of theoretical analysis of literary sources and data categorization. The PubMed and Research Gate databases were utilized to gather and examine scientific material. Results and conclusions. It has been confirmed that the current research in freestyle acrobatics is centered around the development of innovative systems for monitoring the physical fitness of elite athletes. These systems take into account specific fitness indicators, their relative importance, and a scale of reference values. The use of this model has allowed us to create a model for elite athletes. Another significant area of research is the use of computer modeling, which has revealed that the main limitation in the twisting technique of acrobats is the increased frontal moment of inertia of the body due to the use of sports equipment. Sports biomechanics focuses on the analysis of the phase structure of competitive exercise techniques in acrobatics. The importance of incorporating exercises that target the core stabilizer muscles, which enhance the landing kinetics of freestyle skiers, is emphasized. The moguls emphasize the significance of developing explosive power among elite moguls.. In certain freestyle disciplines, it is crucial to consider the impact of landing on the muscles of athletes. The findings presented here can be valuable for coaches and professionals in enhancing the training of freestyle skiers.